Design of and rationale for the Japan Diabetes Optimal Integrated Treatment study for 3 major risk factors of cardiovascular diseases (J-DOIT3): a multicenter, open-label, randomized, parallel-group trial. Issue 1 (25th January 2016) - Ueki, Kohjiro; Sasako, Takayoshi; Kato, Masayuki; Okazaki, Yukiko; Okahata, Sumie; Katsuyama, Hisayuki; Haraguchi, Mikiko; Morita, Ai; Ohashi, Ken; Hara, Kazuo; Morise, Atsushi; Izumi, Kazuo; et al.
Abstract : Objective: Multifactorial intervention including the management of levels of blood glucose (BG), blood pressure (BP), and lipids has been suggested to decrease cardiovascular disease (CVD) risk. However, the target ideal and feasible levels for these individual parameters have not been fully evaluated. In this study, we examine the hypothesis that stricter control compared with the current targets in the Japanese guideline for BG, BP, and lipids could efficiently and safely reduce CVD risk. Research Design and Methods: We screened patients with type 2 diabetes and hypertension and/or dyslipidemia among 81 hospitals in Japan and allocated them into 2 groups: the intensive therapy group (ITG) and the conventional therapy group (CTG). For the 2 respective groups, the target for glycated hemoglobin (HbA1c) is <6.2% (44 mmol/mol) and <6.9% (52 mmol/mol), for BP it is <120/75 mm Hg and <130/80 mm Hg, and for low-density lipoprotein cholesterol it is <80 mg/dL (<70 mg/dL in the presence of CVD history) and <120 mg/dL (<100 mg/dL in the presence of CVD history). The primary end point is the occurrence of CVD events or death by any cause. These patients are scheduled for stepwise intensifications of medication for BG, BP, and lipid control in the ITG, until the number of primary end point events reaches 250. Results: We recruited 2542 patients and randomly allocated 1271 into the ITG and 1271 into the CTG between June 2006 and March 2009. The mean HbA1c was 8.0% (64 mmol/mol) and the mean duration of diabetes was 8.3 years. Conclusions: This randomized controlled study will test the hypothesis that strict multifactorial intervention therapy is effective for the prevention of CVDs in patients with type 2 diabetes who are at high CVD risk. Trial registration number: NCT00300976.